Taxes, R&D Expenditures, and Open Innovation: Analyzing OECD Countries - Daniel Balsalobre-Lorente; Ayoub Zeraibi; Khurram Shehzad; José María Cantos-Cantos (Journal of Open Innovation: Technology, Market and Complexity, 2021)
This paper aims to measure the effect of tax contributions in promoting innovation while highlighting the role of corporate taxes in governance quality in nations within and outside the Organization for Economic Co-operation and Development (OECD). The study applied the generalized method of moments (GMM) framework and found that good governance invariably increases the Innovation Index. Moreover, research and development expenditures revealed a positive association with the Innovation Index. However, corporate taxes and taxes paid by the business sector harm the Innovation Index. Following the investigation, we recommended that policymakers should plan well to balance the costs of innovation and tax incentives, to avoid stimulating unproductive innovations or affecting operating budgets.